A quantitative analysis of Japan's optimal power generation mix in 2050 and the role of CO2-free hydrogen. (15th December 2018) - Matsuo, Yuhji; Endo, Seiya; Nagatomi, Yu; Shibata, Yoshiaki; Komiyama, Ryoichi; Fujii, Yasumasa
Abstract: In this study, the authors developed an Optimal Power Generation Mix model, which takes into account the supply chain of imported and domestically produced hydrogen, also modeling the intermittency of renewable energy at a 10-min resolution, and applied it to the case of Japan, to investigate quantitatively the possibility of achieving zero emission in 2050. Even if the costs of wind and solar PV decline drastically towards 2050 and the huge potentials that have been assumed in the literature are realized, the total system costs escalate significantly with very high shares of intermittent renewables. Since the use of hydrogen produced by excess electricity from renewable power generation sources can only make a slight contribution to reducing this escalation, it would be invaluable to introduce at least a significant amount of electricity generated by "zero-emission thermal power" technologies, including CO2 -free imported hydrogen or conventional thermal power generation with carbon capture and sequestration (CCS). Nuclear power is also estimated as being effective in reducing the cost hike associated with achieving zero emissions. The results of this study could contribute to giving insights regarding global deployment of hydrogen-related technologies, as well as to presenting a frame of reference for Japan's future energy policies. Highlights: Variable renewables can contribute greatly to zero emission power in 2050 in Japan. A very high share of them, however, could escalate the total cost to 20–30 JPY/kWh. "Zero emission thermal" power generation is a necessity to meet the 2050 target. Use of imported hydrogen is one possibility for zero emission thermal power. Use of nuclear power is also an effective way to reduce the cost escalation.